Pyruvate Accelerates Palladium Reduction by Regulating Catabolism and the Electron Transfer Pathway in Shewanella oneidensis - Cheng, Yuan-Yuan (Appl Environ Microbiol, 2021)
Shewanella oneidensis is a model strain of electrochemically active bacteria (EAB) because of its strong capability of performing extracellular electron transfer (EET) and its genetic tractability. In this study, we investigated the effect of carbon sources on EET in S. oneidensis by using reduction of palladium ions [Pd(II)] as a model and found that pyruvate greatly accelerated Pd(II) reduction compared with lactate by resting cells. Both the Mtr pathway and hydrogenases played a role in Pd(II) reduction when pyruvate was used as a carbon source. Furthermore, in comparison with lactate-feeding S. oneidensis, the transcriptional levels of formate dehydrogenases involved in pyruvate catabolism, the Mtr pathway, and hydrogenases in pyruvate-feeding S. oneidensis were upregulated. Mechanistically, the enhancement of electron generation from pyruvate catabolism and electron transfer to Pd(II) explains the pyruvate effect on Pd(II) reduction. Interestingly, a 2-h time window is required for pyruvate to regulate transcription of these genes and profoundly improve Pd(II) reduction capability, suggesting hierarchical regulation for pyruvate sensing and response in S. oneidensis. IMPORTANCE The unique respiration of EET is crucial for biogeochemical cycling of metal elements and diverse applications of EAB. Although a carbon source is a determinant factor of bacterial metabolism, research into the regulation of the carbon source of EET is rare. In this work, we report pyruvate-specific regulation and improvement of EET in S. oneidensis and reveal the underlying mechanism, which suggests potential targets for engineering and improvement of the EET efficiency of this bacterium. This study sheds light on the regulatory role of carbon sources in anaerobic respiration in EAB, providing a way to regulate EET for diverse applications from a novel perspective.